Wittgenstein: "I can't believe.or rather can't believe it yet" - Kallenberg, Brad J. (International journal for philosophy of religion, 2018)
Wittgenstein's attitude toward Christian believing is more complicated that many philosophers have been led to believe. The hiccup in the received account began as a neglect of Wittgenstein's subject-involving method in philosophy of religion. Wittgenstein's method cannot be subsumed under the rubric of philosophy-as-[quasi-scientific]-explanation. Rather, Wittgenstein's method was subject-involving in the sense that by his own methodology he put himself at existential risk. In 1931 he wrote that "[t]he movement of thought in my philosophizing should be discernible also in the history of my spirit, of its moral concepts & in the understanding of my situation". Apparently, to understand Wittgenstein's method we are right to look closely at his biography. In the following essay I show that during his Norwegian sabbaticals, especially that of 1936-1937, Wittgenstein embodied the very method he advocated in his exploration of Christian believing. This method involved him in an enduring practice of actually praying, in close study of passionate Christian thinkers, and in public confession of his private sins. Although his journey ends shy of Christian believing, the form of his spiritual quest exemplifies the manner in which philosophers of religion ought to consider as internal to the investigation of religious concepts.